The Function Of Zagreb As A Factor Of The Transformation Of The Greater Zagreb Girdle – With A Separate Commentary On Daily Migration - Feletar, Petar (Journal for Geography, 2009)
With an almost monocentric development, the most powerful central functions in Croatia are concentrated in Zagreb. These functions have a powerful influence on the transformation of the area towards which they gravitate. This influence is greatest on the geographic area of the Greater Zagreb girdle area, i.e. Zagreb County. The processes of the transformation of the Greater Zagreb girdle relate above all to the urbanisation and suburbanisation of the area. These processes extend to rural areas in a very spatially differentiated way, depending primarily on the level of development and the spatial distribution of the transport network. Spatial differentiation and the level of urbanisation and suburbanisation in the Zagreb environs are illustrated through an analysis of the intensity and distribution of daily migration in Zagreb and through expressed changes in the spatial distribution of inhabitation. These processes were considered to be in parallel in the period from 1948 to 2001, the period of the most intensive change.